Cecilia Tossounian, La joven moderna in Interwar Argentina: Gender, Nation, and Popular Culture, 1920-1940 - Manzano, Valeria (Prismas - Revista de historia intelectual, 2021)
Cecilia Tossounian, La joven moderna in Interwar Argentina: Gender, Nation, and Popular Culture, 1920-1940, Gainesville, University of Florida Press, 2020, 165 páginas